(untitled) (Research, Society and Development, 2022)
The aquatic environment has suffered anthropic impacts through inadequate dumping from domestic, agricultural and industrial sources. Such waste products become fragmented into microplastics (MPs) which accumulate in these ecosystems and cause impact. This study offers the first evaluation of contamination of the surface water by MPs in the Paraíba River estuary, Paraíba State, northeast Brazil. Monthly surface water samples were performed with a phytoplankton net from March 2019 to February 2020, between Restinga Island and the Cabedelo Harbor, downstream of the estuary. About the abiotic factors tested, tide height and precipitation were inversely proportional to MPs abundance at the water surface. While water transparency, wind speed and direction and volume of filtered water did not affect it significantly. A total of 443 MPs were obtained in 1116.26 m3 of filtered water, with a mean abundance of 1.96 ± 1.44 MP/m3, ranging from 0.33 (September) to 4.76 (January). The results reveal an important incidence of MPs pollution downstream in this system. The predominance of MPs fibers (51%) and fragments (48%) result from the slow, natural breakdown of solid waste, confirming the lack of the proper discarding to trash in the João Pessoa metropolitan region. These findings underscore the need for the implementation of simple mitigating measures, such as basic sanitation to reduce local pollution as well as effective routine assessments from the anthropic impact and from water quality control measures in this and many other Brazilian estuaries.